Made in Baja : the lives of farmworkers and growers behind Mexico's transnational agricultural boom - Zlolniski, Christian (University of California Press, 2019)
"Much of the produce that Americans eat is grown in the Mexican state of Baja California, the site of a multi-billion dollar export agricultural boom that has generated jobs and purportedly reduced poverty and labor migration to the U.S. But how has this growth affected those living there? Based on a decade of ethnographic fieldwork, Made in Baja examines the unforeseen consequences for residents in the region of San Quintín, including the tripling of its population; mushrooming precarious colonia communities lacking basic infrastructure and services; and turbulent struggles for labor, civic, and political rights. Anthropologist Christian Zlolniski reveals the effects of growers structuring the industry around an insatiable demand for fresh fruits and vegetables. He also investigates the ecological damage--'watercide'--and the social side effects of exploiting natural resources for agricultural production. Weaving together stories from both farmworkers and growers, Made in Baja provides an eye-opening look at the dynamic economy developing south of the border"--Provided by publisher.